Lamentation and Modernity in Literature, Philosophy, and Culture - Saunders, R. author. aut Link
XVII, 233 p.
Keywords: Saunders analyzes the ideological uses of loss in literary, philosophical, and social texts from the late 19th and 20th centuries through the lens of women's lament traditions and includes philosophical texts by Nietzsche, Heidegger, and Derrida; and literary works by William Faulkner, Stéphane Mallarmé, Dimitris Hatzis, and Tahar Ben Jelloun.